Burden of tuberculosis at post mortem in inpatients at a tertiary referral centre in sub-Saharan Africa: a prospective descriptive autopsy study. Issue 5 (May 2015) - Bates, Matthew; Mudenda, Victor; Shibemba, Aaron; Kaluwaji, Jonas; Tembo, John; Kabwe, Mwila; Chimoga, Charles; Chilukutu, Lophina; Chilufya, Moses; Kapata, Nathan; Hoelscher, Michael; Maeurer, Markus; et al.
Summary: Background: Patients with subclinical tuberculosis, smear-negative tuberculosis, extrapulmonary tuberculosis, multidrug-resistant tuberculosis, and asymptomatic tuberculosis are difficult to diagnose and may be missed at all points of health care. We did an autopsy study to ascertain the burden of tuberculosis at post mortem in medical inpatients at a tertiary care hospital in Lusaka, Zambia. Methods: Between April 5, 2012, and May 22, 2013, we did whole-body autopsies on inpatients aged at least 16 years who died in the adult inpatient wards at University Teaching Hospital, Lusaka, Zambia. We did gross pathological and histopathological analysis and processed lung tissues from patients with tuberculosis through the GeneXpert MTB/RIF assay to identify patients with multidrug-resistant tuberculosis. The primary outcome measure was specific disease or diseases stratified by HIV status. Secondary outcomes were missed tuberculosis, multidrug-resistant tuberculosis, and comorbidities with tuberculosis. Data were analysed using Pearson χ 2, the Mann-Whitney U test, and binary logistic regression. Findings: The median age of the 125 included patients was 35 years (IQR 29–43), 80 (64%) were men, and 101 (81%) were HIV positive. 78 (62%) patients had tuberculosis, of whom 66 (85%) were infected with HIV. 35 (45%) of these 78 patients had extrapulmonary tuberculosis. The risk of extrapulmonary tuberculosis was higher among HIV-infected patients than among uninfected patients (adjusted odds ratio 5·14, 95% CI 1·04–24·5; p=0·045). 20 (26%) of 78 patients with tuberculosis were not diagnosed during their life and 13 (17%) had undiagnosed multidrug-resistant tuberculosis. Common comorbidities with tuberculosis were pyogenic pneumonia in 26 patients (33%) and anaemia in 15 (19%). Interpretation: Increased clinical awareness and more proactive screening for tuberculosis and multidrug-resistant tuberculosis in inpatient settings is needed. Further autopsy studies are needed to ascertain the generalisability of the findings. Funding: UBS Optimus Foundation, EuropeAID, and European Developing Countries Clinical Trials Partnership (EDCTP).